An ethnomathematics study at Palang fish auction site - Alfiyah, Khusnul; Warli, Warli (Universitas Islam Negeri Raden Intan Lampung, 2024)
The fish auction site in Palang is an integral part of the daily lives of the fishermen community in Palang and reflects local wisdom. Mathematics is a part of human activity, and ethnomathematics can serve as a bridge connecting mathematics with local wisdom. This qualitative study aims to describe the ethnomathematics present at the Palang fish auction site. Observation and interview methods were used to collect data, which were then analyzed descriptively and qualitatively. The study's results show that in the counting aspect, arithmetic concepts were identified; in the locating aspect, geometric transformation concepts were found; in the measuring aspect, measurement concepts were obtained; and in the designing aspect, geometric concepts were discovered. This research has implications as an alternative resource for learning media, practice exercises, and assessment in elementary, middle, and high school education. Future research can further develop these findings to enhance students' motivation and understanding of mathematics.